Analysis of Stability in Static Signatures Using Cosine Similarity - Impedovo, D.; Pirlo, G.; Sarcinella, L.; Stasolla, E.; Trullo, C. A. (2012 International Conference on Frontiers in Handwriting Recognition, 2012)
This paper presents a new technique for the analysis of stability in static signature images. The technique uses an equimass segmentation approach to non-uniformly split signatures into a standard number of regions. Successively, a multiple matching technique is adopted to estimate stability of each region, based on cosine similarity. The GPDS database has been considered for the experimental test. The results demonstrate the validity of the novel approach and highlight some directions for further research.